THE EFFECT OF OPERATIONS CASH, NET PROFIT, AND DEBT TOWARD THE DEVIDENTIC POLICY ON MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Suryani Suryani; Suradi Suradi; Ratna Wulandari (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2021)
ABSTRACT This study aims to determine the influence of operation cash flow, net profit, and debt toward the devidentic policy on manufacturing companies listed on the Indonesia Stock Exchange. The research population is manufacturing companies listed on Indonesia Stock Exchange, and continues to distribute dividends to shareholders during the observation period 2015-2018. The sampling technique used in this study is the purposive sampling method and based on the technique, the number of samples that meet the requirements is 10 companies with a period of 4 years (2015-2019), so the number of samples is 40 companies. The analytical method used is Multiple Linear Regression Analysis. The results of study are 1) based on the results of the T Test, the T calculated operation cash flow is 3,026 because the value of T arithmetic 3.026 > T table 1.69 then Ho or the first hypothesis is rejected, it means that there is a partial influence between operation cash flow and dividend policy, 2) based on the results of the T Test, T calculate net profit obtained by -1,451 because the value of T count -1.451 < T table 1.69 then Ho or the first hypothesis is accepted, it means that there is no partial influence between net profit and dividend policy, 3) based on the results of the T-Test, the T-calculated debt obtained by -1,241 because the value of T count -1,241 < T table 1.69 then Ho or the first hypothesis is accepted, it means that there is no partial influence between debt and dividend policy, and 4) based on the F Test, the F calculated independent variable is 6.115 because the F value is 6.115 > F table 2.87, Ho or the first hypothesis is rejected, it means that there is a simultaneous influence between operation cash flow, net profit, and debt toward the devidentic policy. . Keywords: operation cash flow, net profit, debt, and dividend policy